Association between triglyceride glucose index and breast cancer in 142,184 Chinese adults: findings from the REACTION study - Wu, Xueyan; Wang, Shuangyuan; Lin, Lin; Jia, Xiaojing; Hu, Chunyan; Qi, Hongyan; Lin, Hong; Zheng, Ruizhi; Li, Mian; Xu, Yu; Xu, Min; Chen, Lulu; et al. (Frontiers in Endocrinology, 2024)
Background: The Triglyceride Glucose (TyG) index has been associated with an increased risk in breast cancer. However, this association remains unclear among the Chinese population. This study aimed to investigate whether the TyG index is associated with the risk of prevalent breast cancer in Chinese women. Methods: This cross-sectional study included 142,184 females from the REACTION (Risk Evaluation of Cancers in Chinese Diabetic Individuals: A Longitudinal) Study, which recruited adults aged 40 years or older from 25 centers across mainland China between 2011 and 2012. The TyG index was calculated according to the formula: Ln (fasting triglycerides [mg/dL] ×fasting glucose [mg/dL]/2). Multivariable-adjusted logistic regression models were used to evaluate odds ratios (ORs) and 95% confidence intervals (CIs) regarding the associations between the TyG index and breast cancer. Results: Multivariable-adjusted logistic regression analysis showed that compared with the lowest quartile of TyG index, the highest quartile of TyG index was significantly associated with an increased risk of prevalent breast cancer, with an OR (95% CI) of 1.61 (1.19-2.17). In the stratified analysis, the association of each 1 SD increase in TyG index with risk of prevalent breast cancer was more dominant in individuals with menarche at age 13-17, those who were postmenopausal, those with a history of breastfeeding and had 2-4 children, with the ORs (95% CIs) of 1.35 (1.09-1.68), 1.27 (1.05-1.54), 1.26 (1.05-1.52) and 1.32 (1.08-1.62), respectively. Moreover, among those without discernible insulin resistance (homeostatic model assessment-insulin resistance [HOMA-IR] ≥ 2.5), hyperglycemia and dyslipidemia, each 1 SD increase in TyG index was associated with a 1.36-fold increase in breast cancer risk, with an OR (95% CI) of 2.36 (1.44-3.87). Conclusions: The TyG index is significantly associated with the prevalent breast cancer risk among middle-aged and elderly Chinese women.